Preservice Elementary Mathematics Teachers’ Noticing Task Design in Video Analysis - Wiputra Cendana; Kimura Patar Tamba; Sean Patrick Kang; Khoe Yao Tung (Program Studi Pendidikan Matematika Universitas PGRI Kanjuruhan Malang, 2026)
Pre-service elementary mathematics teachers can learn about task design through noticing. For this reason, it is very important to understand and analyze the noticing ability of pre-service elementary mathematics teachers. This study is a qualitative descriptive study that aims to analyze the results of pre-service elementary mathematics teachers’ noticing of task design using video. The participants in this study were 35 pre-service elementary mathematics teachers in one of the private universities in Tangerang. Pre-service elementary mathematics teachers' noticing data were collected from the results of video task analysis on task design. Data analysis was carried out using theoretical coding method on the results of the video task analysis. Pre-service elementary mathematics teachers’ noticing of task design is not comprehensive. Pre-service elementary mathematics teachers tend to only focus on one or two aspects of task design. The focus of pre-service elementary mathematics teachers’ noticing is the mathematical activity involved aspect. The results of this study also show that pre-service elementary mathematics teachers’ noticing quality is at the artificial level.